PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP SEMANGAT KERJA PARAMEDIS RUMAH SAKIT NUSALIMA PEKANBARU - Diana Handayani; Susi Hendriani; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at the Nusalima Hospital Pekanbaru. This study aims to determine the influence of Leadership and Supervition or partially on Paramedics’s employee morale at the Nusalima Hospital Pekanbaru. The population in this study were all full-time paramedics at the Nusalima Hospital Pekanbaru, amounting to 45 people. The entire members of the study population were taken as respondents, so that the sampling method of analysis used in this study is the method of multiple linear regression analysis using SPSS 19. The result of this study indicate that both variables, Leadership and Supervition, simultaneously give significant effect on paramedics’s employee morale. Partially it shows that Leadership variables significantly influence Paramedics’s Employee Morale. It can be concluded that Leadership and Supervition variables simultaneously and partially have positive and significant impact on Paramedics’s Employee Morale at Nusalima Hospital Pekanbaru.Keywords: Leadership , Supervition and Employee Morale